Research Sequential Relationship of Appeal, Attitude, Ethical Judgement and Purchase Intention a A SEM Analysis (Global Journal of Management and Business Research, 2013)
The use of sex appeal in advertisements is widely preferred by marketers around the globe as they believe 'sex sells'. Less Academic attention is devoted to explain how an appeal like sex works among Indian audience and what are the mediating variables aid in the process of persuasion. This study aims at empirically investigating the complex relationship as well as the sequential effect of 'Sex appeal → Attitudes toward the Ad → Ethical Judgment toward the Ad → Purchase intention'. The research was executed on a sample of 560 respondents from in and around Tamil Nadu and Pondicherry using non-probability Convenience sampling method. Structural Equation Modeling technique (SEM) was employed to examine the complex relationship between variables and Hypotheses. Results indicate Sex appeal advertisements lead to favourable attitude, which in turn influence Ethical Judgment and Purchase Intention.
Keywords: sex appeal; attitude; ethical judgment; purchase intention; SEM